2020
DOI: 10.24136/oc.2020.026
|View full text |Cite
|
Sign up to set email alerts
|

A new method for calculating mirror data asymmetry in international trade

Abstract: Research background: Some statistics are of a bilateral nature. This is how foreign trade data is organized. They are recorded both in the supplier and recipient countries, hence they are called mirror data. The data recorded at both trading partner countries are not the same for different reasons. Such differences between data on the same groups of transactions are often referred to as the asymmetry of mirror data. The information about the value of the flows of goods are of great importance in economic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…We believe that this research will address many socio-economic issues in addition to the financial market analysed here [90]. Among them, we can mention those of interest to the authors, such as unemployment [91,92], corporate sustainability [93,94], or foreign trade [95]. These studies will certainly reveal distortions of hitherto observed regularities.…”
Section: Discussionmentioning
confidence: 92%
“…We believe that this research will address many socio-economic issues in addition to the financial market analysed here [90]. Among them, we can mention those of interest to the authors, such as unemployment [91,92], corporate sustainability [93,94], or foreign trade [95]. These studies will certainly reveal distortions of hitherto observed regularities.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, the development and good financial situation of enterprises in this sector is of vital importance. The functioning of all enterprises is influenced by various factors, e.g., the economic situation of the country, unemployment, investment attractiveness of the region (Roszko-Wójtowicz and Grzelak, 2021), regional business demography (Markowicz, 2014), the sector situation of companies on the stock exchange (Bieszk-Stolorz and Markowicz, 2017a;2017b), or the international trade (Markowicz and Baran, 2020). For this sector, customer preferences, the development of renewable energy sources (Przygrodzki and Kubek, 2021), and environmental protection (Kurian, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Традиционно анализ экспорта страны основан на национальной статистике. Однако несомненный практический интерес представляет анализ этого же потока на базе зеркальной статистики страны пребывания в виде ее импорта [3]. Oценка расхождений в статистическом учете отражения экспорта России и импорта стран -партнеров по внешней торговле и определение партнеров, где эти расхождения высоки, по сравнению с другими, выбранной базы данных на результаты анализа.…”
unclassified
“…стране на общее отклонение показателей внешней торговли по группе стран ЕС рассчитывали долю отклонений по каждому торговому партнеру России[3]:Показатель относительной асимметрии определяли как отношение разницы экспорта России и импорта страны-партнера к средней величине между экспортом России и импортом страны-партнера, выраженное в процентах. В знаменателе формулы использовали среднюю величину, поскольку именно она позволяет не отдавать предпочтения тому или иному статистическому учету, а усреднить возникающие расхождения.Показатель может принимать как положительные, так и отрицательные значения, в зависимости от того, занижены или завышеныТаблица 1построена авторами на основе «Платежный баланс, Международная инвестиционная позиция и внешний долг Российской Федерации» за 2012-2019 гг.…”
unclassified